Beware: Recruitment of Muscle Activity by the EEG-Neurofeedback Trainings of High Frequencies - Paluch, Katarzyna; Jurewicz, Katarzyna; Rogala, Jacek; Krauz, Rafał; Szczypińska, Marta; Mikicin, Mirosław; Wróbel, Andrzej; Kublik, Ewa (Frontiers in Human Neuroscience, 2017)
EEG-neurofeedback became a very popular method aimed at improvement of cognitive and behavioral performance. However, EMG frequency spectrum overlies with higher EEG oscillations and neurofeedback trainings focusing on these frequencies are challenged by the problem of EMG load in the information fed back to the subjects. In such a complex signal it is highly probable that the most controllable component will form the basis for operant conditioning. This might cause different effects in the case of various training protocols and therefore needs to be carefully assessed before designing training protocols and algorithms. In the current experiment a group of healthy adults (n = 14) was trained by professional trainers to up-regulate their beta1 (15-22 Hz) band for eight sessions. Control group (n = 18) underwent the same training regime but without rewards for increasing beta. In half of participants trained to up-regulate beta1 band (n = 7) systematic increase in tonic EMG activity was identified offline, implying that muscle activity became a foundation for reinforcement in the trainings. The remaining participants did not present any specific increase of the trained beta1 band amplitude. The training was perceived effective by both trainers and trainees in all of the groups. These results indicate the necessity of the proper control of muscle activity as a requirement for the genuine EEG-neurofeedback training, especially in protocols that do not aim at participants’ relaxation. The specificity of information fed back to participants should be of highest interest to all therapists and researchers, as it might irreversibly alter the results of the training.